Determinant of financial literacy in laying hens farmers - Asnawi Aslina; Ridwan Muh.; Tenrisanna Vidyahwaty; Wempie; Nirwana; Putri Budi Rahayu Tanama; Sugiarto Mochamad (BIO Web of Conferences)
The ability of farmers to manage their finances and make sound financial decisions is referred to as financial literacy. Financial literacy of laying hens farmers is still relatively low. Some of the determinants that determine financial literacy are related to the demographic requirements of laying hens farmers including education, farming experience, income and working status. The research was conducted in five regencys, namely Gowa, Maros, Soppeng, Sidrap and Enrekang with a sample size of 123 people. The ANOVA is used to test the hypothesis at 5% significance level. The results of the research show that education, frequency of financial transactions, Making Expenditure and Receipt Records, and amount of income are factors that determine the financial literacy of laying hen breeders. This study is expected to be input for decision making and implementing strategies in an effort to increase the level of financial fraud among laying hens farmers.